Isolation of Insect Bacteriocytes as a Platform for Transcriptomic Analyses - Ribeiro Lopes, Mélanie; Simonet, Pierre; Duport, Gabrielle; Gaget, Karen; Balmand, Séverine; Sugio, Akiko; Simon, Jean-Christophe; Parisot, Nicolas; Calevro, Federica (Methods in molecular biology (Clifton, N.J.), 2021)
Over the past few decades, various techniques have been developed and optimized for the accurate measurement of RNA abundance in cells or tissues. These methods have been instrumental in gaining insight in complex systems such as host-symbiont associations. The pea aphid model has recently emerged as a powerful and experimentally tractable system for studying symbiotic relationships and it is the subject of a growing number of molecular studies. Nevertheless, the lack of standardized protocols for the collection of bacteriocytes, the specialized host cells harboring the symbionts, has limited its use. This chapter provides a simple, step-by-step dissection protocol for the rapid isolation of aphid bacteriocytes. We then describe an adapted protocol for efficient extraction and purification of bacteriocyte RNA that can be used for most downstream transcriptomic analyses.